HERITABILITY ANALYSIS OF LOCAL CORN CULTIVARS FROM KISAR ISLAND SOUTHWEST MALUKU AFTER INDUCED WITH COLCHICINE - Sinay, Hermalina; Tanrobak, Jonetha (Biosaintifika: Journal of Biology & Biology Education, 2020)
In the plant breeding program, selection is one process which aimed to obtain some varieties with superior traits. Within this process, one of criteria that must be consider is the wide genetic diversity of the plant which was selected, and how these traits are inherited. The purpose of this research was to determine (1) the influence of cultivar differences and the colchicine concentration towards the growth and production of local corn cultivar from Kisar Island Maluku, (2) to determine the heritability of growth and production variables after induced with colchicine. Completely randomized block design  was used in this research with factorial design that consist of two factors i.e corn cultivar and colchicine concentration. The research procedure starts from field and seed preparation, immersion of seed into the colchicine solution, transplantation of seed into the field, plant maintenance, and  harvesting. The variable measured including growth and production variables of corn. The analysis of variance showed a significant effect of cultivar differences on all growth and production variables (p value > 0.05), while colchicine concentration only showed a significant effect toward the plant height and number of seed per ear.  The heritability analysis result showed that all variables observed were in high category. The different corn cultivars have a significant effect on all the growth and production, while the colchicine concentration only affect the plant height and number of seed per ear, and the heritability were in high category.  This research provides useful information to farmers how to use colchicine to trigger plant growth and production. It can be used as an information in selecting corn cultivars with high yield potential.